How does contact with accountants influence perceptions of accounting - Wells, Paul (The University of Sydney, 2013)
Contact with accountants has often been suggested as a strategy for changing the stereotypical perceptions people have of accounting. This study examines how contact with accountants influences these perceptions. The perceptions of sixteen people who have had no contact with accountants are compared with perceptions of sixteen people who have been the recipients of information from accountants. The perception data was collected by questionnaire and interview. Response data was analysed and compared between the collection techniques and participant groups. The results reveal that while the perceptions do differ between participant groups they are still overgeneralisations and are therefore stereotypical. These findings confirm the claims by social psychologists that while contact may assist in changing perceptions, the change will not necessarily have the desired effect. This has implications for how the profession attempts to alter its image to the public at large.
Keywords: Accounting stereotype; Perceptions; Contact